2013
DOI: 10.1007/s11663-013-9928-3
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Chemical Viscosity Model for Fully Liquid Slag in the Al2O3-CaO-MgO-SiO2 System—Part I: Revision of the Model

Abstract: A model has been developed that enables the viscosities of the fully liquid slag in the multicomponent Al 2 O 3 -CaO-FeO-Fe 2 O 3 -MgO-Na 2 O-SiO 2 system to be predicted within experimental uncertainties over a wide range of compositions and temperatures. The Eyring equation is used to express viscosity as a function of temperature and composition. The model links the activation and pre-exponential energy terms in the viscosity expression to the slag internal structure through the concentrations of various Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Selected BF viscosity models [13][14][15] are reproduced and calculated using the same compositions. The average relative deviations of the present model and other models are calculated and plotted in Fig.…”
Section: Sensitivities Of Viscosity To Major Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected BF viscosity models [13][14][15] are reproduced and calculated using the same compositions. The average relative deviations of the present model and other models are calculated and plotted in Fig.…”
Section: Sensitivities Of Viscosity To Major Componentsmentioning
confidence: 99%
“…Different viscosity models [12][13][14][15][16][17][18] have been proposed to predict the viscosities of BF slags in wide composition range. As significant discrepancies are present for the reported viscosity data, these viscosity models are yet to be developed to accurately predict the viscosities of BF slags.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental viscosity study in the Al 2 O 3 -'FeO'-SiO 2 slag at metallic iron saturation 12,13) showed possible maximum of viscosity at intermediate Al / (Al + Fe) ratios at constant SiO 2 concentrations indicating that the Fe 2+ cation possibly also introduces "the charge compensation effect", similar to the effects by the Ca 2+ and Mg 2+ in the Al2O3-containing systems. 10,11) In addition, noticeable charge compensation effect on the Fe 3+ cation in slags by basic cations such as Na + and Ca 2+ have been reported in previous viscosity experimental 14,15) and analytical 16) studies. Although several structurally-based viscosity models incorporate ferric oxide as chemical components in slag, [17][18][19][20] there is no description of the charge compensation effect on Fe 3+ .…”
Section: Introductionmentioning
confidence: 82%
“…The quasi-chemical viscosity (QCV) model and recent revisions have been presented in detail in previous publications; 1,10) a brief description of the essential features are given below.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation